x → 1 lim x 8 − 1 x 1 3 − 1
Calculate the limit above.
If you think that the limit does not exist, submit your answer as 12.
Note: You can only use algebraic simplification to evaluate the limit, and neither the method of approximation.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It is visible that 1 is a root of the polynomial ( x 1 3 − 1 ) . Then clearly the polynomial has ( x − 1 ) as one of its factors. Similarly ( x 8 − 1 ) also has ( x − 1 ) as one of its factors.
Therefore, by using algebraic division to obtain the other factors, the given polynomial function becomes:
( x − 1 ) ( x + 1 ) ( x 2 + 1 ) ( x 4 + 1 ) ( x − 1 ) ( x 1 2 + x 1 1 + x 1 0 + . . . x 2 + x + 1 )
= ( x + 1 ) ( x 2 + 1 ) ( x 4 + 1 ) ( x 1 2 + x 1 1 + x 1 0 + . . . x 2 + x + 1 )
Here, we can substitute x = 1 such that the limit doesn't stand out to be undefined. Hence, by substituting we have the limit of the function as 8 1 3 , while x tends to 1 .
Use L-Hospital's rule to evaluate the limit because you first get 0/0 which is indeterminate. So, evaluate limit as x approaches 1 of 13x^12 / 8x^7 , which is 13/8
Problem Loading...
Note Loading...
Set Loading...
It's a limit with form 0 0 undetermined. x → 1 lim x 8 − 1 x 1 3 − 1 = x → 1 lim ( x − 1 ) ( x 7 + x 6 + x 5 + . . . . + x + 1 ) ( x − 1 ) ( x 1 2 + x 1 1 + x 1 0 + . . . + x + 1 ) = x → 1 lim x 7 + x 6 + x 5 + . . . . + x + 1 x 1 2 + x 1 1 + x 1 0 + . . . + x + 1 = Now, substituing at x = 1 = 8 1 3 = 1 . 6 2 5